Quality of Machined Wood Surfaces - Csanády, Etele; Magoss, Endre; Tolvaj, László (Springer International Publishing : Imprint: Springer, 2015)
The purpose of this monograph is to characterize and describe the quality of machined wood surfaces, whereas particular attention is given to the utility and to aesthetical values in product design. The approach employed by the authors involves an introductory overview and is then organized in three parts: first, the book deals with factors influencing surface stability, the second part describes the color and gloss properties of wood surfaces with many practical applications, and the third part covers roughness properties of surfaces related to machining. This is a highly informative and carefully presented book, providing valuable insight for both research experts and practitioners with an interest in machined wood surfaces.